Offset Credits in the EU ETS: A Quantile Estimation of Firm-Level Transaction Costs - Helene Naegele (Environmental & Resource Economics, 2018)
International carbon offset certificates were cheaper than European Union Allowances, although they were substitutes within the EU Emissions Trading System (EU ETS). Thus, firms had a strong incentive to use offset certificates. However, a considerable number of firms did not exhaust their offset quota and, by doing so, seemingly forwent profits. While most literature on emissions trading evaluates the efficiency of regulation in a frictionless world, in practice firms incur costs when complying with regulation. In order to assess the relevance of trade-related fixed transaction costs, this study examines the use of international offset credits in the EU ETS. It establishes a model of firm decision under fixed (quantity-invariant) entry costs and estimates the size of such costs rationalizing firm behavior using semi-parametric binary quantile regressions. Comparing binary quantile results with probit estimates shows that high average transaction costs result from a strongly skewed underlying distribution. For most firms, the bulk of transaction costs stems from certificate trading in general, rather than additional participation in offset trading.
Keywords: C25; D23; H23; Q58; 330; Binary quantile estimation; CDM; Carbon emissions trading; Entry costs; EU ETS; Offset certificates; Semi-parametric estimation; Transaction costs